The Role of Islamic Education Teachers in Developing Student Personalities - Susilo, Hari Aji (International Conference of Moslem Society, 2019)
Since birth, humans have had basic desires, namely the desire to be one with the atmosphere of the surrounding environment. At one time, there will be social interaction which will then occur social activities because social interaction is the main requirement for social activities. Islam respects people who work as teachers. Teachers can read socio-religious conditions towards more advanced conditions. This is where the importance of religious teachers to carry out their roles. If someone uses his rights and obligations according to his position, then he takes on the role. If they can use their rights and obligations properly, it can be said otherwise if they have not been able to use their rights and obligations, which means that they have not been able to carry out their roles properly. Professional and skilled educators, dedication and expertise are needed and expected and carry out community development. Islamic religious teachers act and say according to religious norms and society. They are required to collaborate with the community in a compact manner for the success of achieving the desired conditions. The growth and development of the child's personality occur through life experiences both in the family, in school and in the community. The more religious values internalized, attitudes, actions, behaviors, and ways of dealing with life will be in accordance with religious teachings, so that a complete and ideal personality pattern is formed based on religious values.